My hero academia vigilantes. 2 - Furuhashi, Hideyuki, 1971-; Cook, Caleb D. (Shonen Jump manga., 2018)
Not everyone needs a license to fight for justice! In a superpowered society, there is nothing ordinary about evil anymore. Heroes, trained and licensed to protect and defend the public against supervillains, stand above all the rest. Not everyone can be an official hero, however, and there are those who would use their powers to serve the people without legal sanction. But do they fight for justice in the shadows, or for reasons known only to themselves? Whatever they fight for, they are called<U+2026>vigilantes. Koichi and his “friends”<U+2014>Kazuho, a.k.a. Pop Step, and the mysterious Knuckleduster<U+2014>have teamed up to protect their neighborhood (unofficially of course). But even petty criminals with Quirks can be dangerous, and taking them on shows Koichi that he<U+2019>d better not underestimate them. Sizing up the opposition is important, especially when some of the villains are definitely out of Koichi<U+2019>s league and more sinister threats lurk in the shadows<U+2026>